Atividade in vitro Anti-Pythium insidiosum do cloridrato de amorolfina e azitromicina isoladamente e em combinação - Ianiski, Lara Baccarin (2020)
Pythium insidiosum, belonging to the Kingdom Stramenopila (super group Stramenopiles- Alveolata-Rhizaria - SAR), Class Oomycetes, Order Pythiales, Family Pythiaceae, Genus Pythium and Species Pythium insidiosum is the etiological agent of pythiosis, a chronic granulomatous disease, usually fatal, capable of infecting animals and humans. It is occurring in tropical, subtropical, and temperate areas. Pythiosis is commonly reported in humans in Southeast Asia, mainly in Thailand. Conversely, in Brazil, pythiosis affects mostly equines and it is more prevalent in Pantanal Mato-Grossense and Rio Grande do Sul. This oomycete has characteristics that distinguish it from fungi, especially the incomplete ergosterol biosynthesis pathway, the main target of action of existing antifungal drugs, making it less susceptible to commercially available chemotherapeutic therapies. In an attempt to establish an efficient therapeutic protocol for the control of this disease, therapeutic possibilities to combat infections by P. insidiosum have been widely evaluated. Thus, this study evaluated the in vitro susceptibility profile of P. insidiosum isolates (n = 20) against amorolfine hydrochloride (AMR) and azithromycin (AZM) alone and in combination. The susceptibility tests were performed according to CLSI protocol M38-A2 and the combinations were evaluated by the checkerboard microdilution method. In addition, scanning electron microscopy and transmittance were performed in order to verify the effects on the isolates treated with the drugs. All P. insidiosum isolates evaluated showed minimum inhibitory concentration (MIC) ranging from 16 to 64 mg/L when using AMR and from 8 to 64 mg/L for AZM. Synergistic interactions were not observed, showing 59.8% antagonism and 36.2% indifferent interactions. The scanning electron microscopy and transmittance analyzes showed changes in the surface of the hyphae of P. insidiosum, disorganization of the intracellular organelles, as well as changes in the plasma membrane and cell wall when the microorganism was treated with both drugs. The use of drugs alone presented significant therapeutic potential for the treatment of pythiosis. This is the first study to demonstrate the in vitro activity of AMR, as well as to evaluate its combination with AZM against P. insidiosum. Thus, this drug may represent a therapeutic potential to be further investigated against cutaneous and subcutaneous forms of pythiosis.